Clinical Features and Outcomes of Acute Chlorine Gas Inhalation; a Brief Report - Ejaz, Taymmia; Saadia, Sheema; Akhlaq, Safia; Aziz, Adil; Ahmed, Muhammad Arslan; Siddiqui, Aisha Fareed (Archives of Academic Emergency Medicine, 2022)
Methods: This retrospective cross-sectional study, evaluated the clinical features and outcomes (length of hospital stay, complications, and mechanical ventilation requirement) of patients presenting to ED of Aga Khan University Hospital, Karachi, Pakistan, with history of chlorine gas exposure at the Engro Plant from 6th March to 14th March 2020. Results: 38 patients with mean age of 33.1 ± 8.1 years presented to ED with history of chlorine gas exposure (100% male). 4 (10.5%) cases had comorbid diseases. Most common presenting symptom was dyspnea, observed in 33 (86.8%) cases, followed by cough, seen in 27 (71.1%) subjects. 13.2% (5/38) patients had infiltration on chest x-ray and 33 (86.8 %) required hospitalization. 6 (15.8%) patients had repeat presentation requiring hospitalization or ED visit. 18 (47.4%) were managed with high flow oxygen therapy, 9 (23.7%) required non-invasive ventilation and one patient was intubated due to development of pneumo-mediastinum. Mean length of stay was 1.55 ± 1.58 days and no patients died. Presence of tachycardia was the only finding significantly associated with need for oxygen (p = 0.033) and non-invasive ventilation (p = 0.012). Conclusion: The majority of patients presenting with acute chlorine gas exposure showed good clinical outcomes and rapid recovery, however, a high index of suspicion and vigilance should be maintained for complications such as pneumomediastinum and acute respiratory distress syndrome in these patients.